Reporting Public Opinion - Larsen, Erik Gahner. author. aut Link
XIV, 134 p. 21 illus., 4 illus. in color.
Keywords: This book is about how opinion polls are reported in the media. Opinions polls are not reported in the media as unfiltered numbers, and some opinion polls are not reported at all. This volume demonstrates how opinion polls travel through several stages that eventually turn boring numbers into biased news in the media. The framework offered in this book helps to understand how some polls end up in the news coverage, and which systemic biases abound in the news media reports of opinion polls. In the end, a change narrative will be prominent in the reporting of opinion polls which contributes to what the general public sees and shares. The findings cover journalists, politicians, experts and the public, and how they all share a strong preference for change. Erik Gahner Larsen is Senior Scientific Adviser at the Conflict Analysis Research Centre, University of Kent, UK. Zoltán Fazekas is Associate Professor of Business and Politics, with focus on quantitative methods in the Department of International Economics, Government and Business at the Copenhagen Business School, Denmark. .